Tahfiz (Memorization Sciences) Curriculum Practice: An Empirical Study from Private School in Johor, Malaysia - Abd Rahman Abd Ghani; Miftachul Huda; Maidatus Sholihah; Tabrani ZA; Hayati Hussin (Nazhruna: Jurnal Pendidikan Islam, 2025)
As part of memorization sciences, Tahfiz on the Quran has been widely emerged in the Malay Archipelago where mostly all its institutions managed by bodies or individuals privately. This study aims to examine the assessment of implementation of the curriculum, also involves the form and method of curriculum implementation available in these institutions, especially institutions located in the state of Johor. The study data was obtained through a questionnaire instrument distributed to 25 institutions in the state of Johor. Of the total, only 19 forms were returned and that number was analyzed to obtain the percentage of implementation of the private Tahfiz curriculum in the state of Johor. The data obtained were processed using Statistical Package for Social Science (SPSS) version 16.0. The findings of the analysis show that the two items involving the form of Tahfiz curriculum and the implementation method of Tahfiz curriculum are at a less satisfactory level of interpretation that is medium low. Although there is one item related to the implementation of the curriculum in the state of Johor is at a moderately high level of interpretation, but if evaluated as a whole, the level of implementation is still at a moderately low level of interpretation. Therefore, this study found that there are some specific aspects, especially those involving the form and method of implementation need to be improved so that the curriculum offered is able to produce a generation of knowledgeable, skilled and competitive huffaz (memorizer).